PENGEMBANGAN DAYA SAING SENTRA INDUSTRI KECIL MELALUI PENDEKATAN KLASTER INDUSTRI DINAMIS (STUDI PADA SENTRA INDUSTRI MEBEL DI KAMPUNG KEMIRAHAN, KELURAHAN TUNJUNGSEKAR, PURWODADI, POLOWIJEN KOTA MALANG) - Tia Amelia (Jurnal Ilmiah Mahasiswa FEB, 2015)
The competitiveness of industrial center in Kemirahan Malang currently leads to the development of product innovation rather than the efficient of cost. This research aims to analyze the variables which influence the competitiveness industry such as resources variable, related industry and supplier, the strategy of company and competitors, and the variable condition of demand. The data analysis which used is Partial Least Square with the help of SmartPls 3.0 program. This research measure 2 types of model those are Measurement Model (Outer Model) and Structural Model (Inner Model).The test result of measurement model stated that the indicator after being modified is valid and reliable in measuring laten variable (resources variable, related industry and supplier, the strategy of company and competitors, and the variable condition of demand). Each of indicator has a loading factor rate > 0,7, AVE > 0,5, Croanbach’s alpha > 0,7, Composite Reliability > 0,.The result of structural measurement stated that the rate of R-Square amounts 0,89 percent, the independent variable which influence obvious (significance) towards the variable of industrial competitiveness (Y) in the level of confidence 95% is the competitiveness variable with the coefficient path amounts 1,036.Keywords : Competitiveness, Cluster, Industry, Innovation, Cost Leadership.